2010
DOI: 10.3109/14992020903431280
|View full text |Cite
|
Sign up to set email alerts
|

Self-assessed auditory symptoms, noise exposure, and measured auditory function among healthy young Swedish men

Abstract: The aim of the study was to estimate the prevalence of the exposure to ototraumatic factors and auditory symptoms, and to analyse the relations between these factors in a group of young healthy men. A total of 839 men, 19-22 years old, were recruited for the study when reporting for primary military service. A questionnaire was distributed and audiometry was performed. The prevalence of tinnitus, sensitivity to noise, and measured hearing impairment in the study group was 23.2%, 15.5%, and 14.5% respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 19 publications
2
33
1
6
Order By: Relevance
“…Among the musicians, an association between number of hours of instrumental practice and impaired hearing was found (Hagberg et al, 2005). Occupational noise was reported by over 50% of males aged 19-22 doing their military service, and an association was found between occupational noise and hearing deterioration (Muhr and Rosenhall 2010). Conclusion: In studies based on young workers in the Nordic countries there is limited evidence suggesting an association between occupational noise and impaired hearing.…”
Section: Discussionmentioning
confidence: 90%
“…Among the musicians, an association between number of hours of instrumental practice and impaired hearing was found (Hagberg et al, 2005). Occupational noise was reported by over 50% of males aged 19-22 doing their military service, and an association was found between occupational noise and hearing deterioration (Muhr and Rosenhall 2010). Conclusion: In studies based on young workers in the Nordic countries there is limited evidence suggesting an association between occupational noise and impaired hearing.…”
Section: Discussionmentioning
confidence: 90%
“…Henderson et al, 2011: 12.7%;Shargorodsky et al, 2010: 16.4%;Niskar et al, 1998: 12.7%). Only Muhr & Rosenhall (2010) found a lower fi gure (7.4%), but this is probably due to a different defi nition of the critical hearing threshold (20 dB HL instead of 15 dB HL, like the authors above). On the other hand, the relatively high fi gure reported from Shargorodsky et al (2010) may result from the inclusion of the 8-kHz frequency into the series of test frequencies.…”
Section: Discussionmentioning
confidence: 79%
“…On the other hand, some studies failed to establish an association between exposure to loud music and hearing defi cits (e.g. Carter et al, 1982;Johnson et al, 1986;Williams, 2005;Muhr & Rosenhall, 2010;Shargorodsky et al, 2010;Henderson et al, 2011). In addition, several studies revealed that the prevalence of hearing loss in young adults did not signifi cantly change over the past decades (Rabinowitz et al, 2006;Augustsson et al, 2006;Henderson et al, 2011), while at the same time their exposure to loud music increased (Smith et al, 2000;Serra et al, 2005;Henderson et al, 2011).…”
mentioning
confidence: 96%
“…Four studies considered the mean of three frequencies (i.e. 500Hz, 1Khz and 2Khz) and established the mild hearing loss from 26dB 15,16,18,24 . The studies using the cutoff point for mild hearing loss from 26dB showed greater variability in the prevalence of hearing loss: 7.1 to 23.8%…”
Section: Resultsmentioning
confidence: 99%
“…Five papers considered high frequency tonal threshold, classifying mild hearing loss from 16dB and observed prevalence near 15% [24][25][26][27][28][29] . Four studies considered the mean of three frequencies (i.e.…”
Section: Resultsmentioning
confidence: 99%